PENERAPAN HAZARD ANALYSIS AND CRITICAL CONTROL POINT (HACCP) PADA PROSES PRODUKSI WAFER ROLL [Implementation of Hazard Analysis and Critical Control Point (HACCP) in Production of Wafer Roll] - Ardaneswari Dyah Pitaloka Citraresmi; F. P. Putri (Jurnal Teknologi & Industri Hasil Pertanian, 2019)
The purpose of this study was to determine the application of Hazard Analysis and Critical Control Points (HACCP) to identify and prevent potential hazards in the production process of chocolate roll wafers at PT. X.  The production process of wafer roll at PT. X consisted of mixing raw materials, filtering, roasting, rolling a wafer roll, filling cream, cutting, decreasing wafer roll temperature, packaging, and X-ray detection.  The implementation of a quality assurance system must be carried out at every stage of processes to prevent microbiological chemical, and physical hazard pollution, and maintaining product quality.  The study was conducted using a survey method, by directly following the entire process of making chocolate roll wafers from the receiving of raw materials to the final product in the packaging.  The data was analyzed using descriptive analysis method.  The application of the HACCP system at PT. X through two steps, that were preliminary hazard analysis step and hazard analysis step.  The results showed that the X-ray detection pathway found CCP contamination of foreign objects with significant hazards in the form of metal parts in the product.  Preventive actions taken included separating and marking deviant products, repairing the auto stop system, and visual observation by employees on X-ray detection machines.